Kontrol Kesehatan, Promkes dan Aktifitas Fisik Pada Lansia Wilayah Puskesmas Banjarbaru Utara Dan Martapura1 - Ilmi, Bahrul; Fauziah, Erna; Rizani, Akhmad (UPPM Poltekkes Kemenkes Banjarmasin, 2023)
Angka tertinggi Covid-19 kelurahan Banjarbaru Utara, sebanyak 2237 kasus, dipantau 110, dirawat 24 orang sumber data Dinas Kesehatan Kota Banjarbaru (2022) Hipertensi dan Diabetes merupakan komorbid yang dapat memperparah infeksi virus Covid-19, dan menjadi penyebab kematian tertinggi pada penderita Covid-19 berdasarkan laporan CNN Indonesia (2020). Tujuan melaksanakan peningkatan kapasitas Lansia melalui Kontrol kesehatan, promosi kesehatan; konsep Era Normal Covid-19, pentingnya menjaga imun tubuh, dan penyakit komorbid Hipertensi serta melakukan aktifitas fisik. Abstract: The highest number of COVID-19 cases in the North Banjarbaru sub-district is 2,237 cases, 110 monitored and 24 people treated (Banjarbaru City Health Office, 2022). Elderly health problems include rheumatoid arthritis due to increased uric acid, high blood pressure, and diabetes mellitus. This is because it is said that hypertension and diabetes are co-morbidities that can exacerbate infection with the Covid-19 virus and are the highest cause of death in sufferers of Covid-19. (CNN Indonesia, 2020). The aim of carrying out capacity building for the elderly through health control, and health promotion, the concept of the Covid-19 Normal Era, the importance of maintaining the body's immunity, and comorbid hypertension and physical activity. Results of community service: hypertension in the elderly is quite high, as much as 47%, with the risk of comorbid COVID-19, heart disease, and stroke. Elderly examination results for Glucose increased up to 19%, Cholesterol increased to 88%, and Uric Acid up to 33%. Health control, counseling, gymnastics for the elderly, and anti-stroke do not necessarily reduce blood pressure in the elderly, but they can still maintain their health so that blood pressure is within normal limits.